1983
DOI: 10.1007/bf00199705
|View full text |Cite
|
Sign up to set email alerts
|

Circulating immune complexes in malignant diseases increased detection rate by simultaneous use of three assay methods

Abstract: By using three different assay methods, circulating immune complexes have been detected in 85% of sera from patients with malignant melanoma, and in 77% of sera from patients with breast cancer. These methods were a C1q-binding assay, a double-antibody conglutinin-binding ELISA, and a polyethylene glycol 6000 precipitation technique followed by quantitative determination of immunoglobulins in the redissolved precipitate. Detection rates of circulating immune complexes using any one of these methods separately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…No single test meets these criteria. This may be due to variations in the composition of ICs and to differing biological and physicochemical properties of ICs [11,27,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No single test meets these criteria. This may be due to variations in the composition of ICs and to differing biological and physicochemical properties of ICs [11,27,29].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the heterogeneity of CICs, parallel application of methods based on different principles may be a useful approach [6,8,11,131. Collective experience in the measurement of CIC has shown that no single method is ideal in all circumstances and that valuable information can be derived from the use of two or more test systems [13,22,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CIC was determined using the polyethylene glycol (PEG) precipitation method in a Beckman Coul ter DU 8 UV spectrophotometer (Beckman Coulter, USA) (6). In brief, 0.2 mL of serum was mixed in 1.8 mL of PEG (37.5 g/L) followed by incubation at 4 °C for 1 h and subsequent centrifugation at 600 ×g for 15 min.…”
Section: Detection Of Cic Concentrationmentioning
confidence: 99%
“…U bolesnika sa malignim melanomom, karcinomom dojke i plu}a, leukemijama i Hodgkinovim limfomom pokazano je da je porast nivoa imunih kompleksa u serumu bolesnika povezan sa pove}anjem tumorske mase, pojavom metastaza odn. lo{om prognozom 9,10,11 . U bolesnika sa karcinomom larinksa takodje je nadjena po-ve}ana kon}entracija blokiraju}ih serumskih faktora 7,12,13 .…”
unclassified